Beginning Oracle PL/SQL - Bales, Donald (Apress : Imprint: Apress, 2015)
Beginning Oracle PL/SQL gets you started in using the built-in language that every Oracle developer and database administrator must know. Oracle Database is chock-full of built-in application features that are free for the using, and PL/SQL is your ticket to learning about and using those features from your own code. With it, you can centralize business logic in the database, you can offload application logic, and you can automate database- and application-administration tasks. Author Don Bales provides in Beginning Oracle PL/SQL a fast-paced and example-filled tutorial. Learn from Don's extensive experience to discover the most commonly used aspects of PL/SQL, without wasting time on obscure and obsolete features. The author takes his 20+ years of experience and a wealth of statistics he's gathered on PL/SQL usage over those years and applies the 80/20 rule: cover what's most needed and used by PL/SQL professionals and avoid what's not necessary! The result is a book that covers all the key features of PL/SQL without wasting your time discussing esoteric and obsolete parts of the language. Learn what really matters, so that you can get to work feeling confident with what you know about PL/SQL. Covers the key topics that matter, including variables and datatypes, executing statements, working with cursors, bulk operations, real-world objects, debugging, testing, and more. Teaches you to write production-level, object-oriented PL/SQL. You'll explore relational PL/SQL, but unlike most other books on the subject, this one emphasizes the use of PL/SQLs object-oriented features as well. Guides you in working through real examples of using of PL/SQL. You'll learn PL/SQL by applying it to real-world business problems, not by heavy theory.